CXCL14 in prostate cancer: complex interactions in the tumor microenvironment and future prospects - Lei Tang; Xin Chen; Jianquan Hou; Xuedong Wei (Journal of Translational Medicine)
Abstract CXCL14 is a highly conserved chemokine expressed in various cell types, playing crucial roles in both physiological and pathological processes, including immune regulation and tumorigenesis. Recently, the role of CXCL14 in tumors has attracted considerable attention. However, previous pan-cancer studies have reported inconsistencies regarding the effects of CXCL14 on tumors, particularly concerning its expression levels in tumor tissues and its influence on various phenotypes of cancer cells. This variability is believed to stem from the context-dependent nature of CXCL14, as different sources of CXCL14 and its secretion within distinct tumor microenvironments may mediate diverse biological effects. Such phenomena have also been observed in prostate cancer research. Despite a foundational understanding of CXCL14 in prostate cancer, there remains a lack of comprehensive reviews summarizing the specific roles of this chemokine and systematically analyzing the reasons behind its complex effects. Therefore, this article aims to discuss the role of CXCL14 in the tumor microenvironment of prostate cancer and explore future research directions and potential applications.